Morphological and phylogenetic analyses reveal a new genus and two new species of Tubakiaceae from China - Zhaoxue Zhang (Pensoft Publishers, 2021)
Species of Tubakiaceae have often been reported as plant pathogens or endophytes, commonly isolated from a wide range of plant hosts. The isolated fungi were studied through a complete examination, based on multilocus phylogenies from combined datasets of ITS/LSU/rpb2 and ITS/tef1/tub2, in conjunction with morphological characteristics. Five strains isolated from Lithocarpus fohaiensis and Quercus palustris in China represented a new genus of Tubakiaceae, Obovoideisporodochium and three species, viz. Obovoideisporodochium lithocarpi sp. nov., Tubakia lushanensis sp. nov. and T. dryinoides.